Criminal Sanctions As an Eradication Strategy Of Corruption: A Critical Study from the Perspective of Islamic Criminal Law - Mohammad Darudin (Al-Ahkam: Jurnal Ilmu Syari’ah dan Hukum, 2018)
The spirit of anti-corruption movement  has been a motion since reformation era in 1998 and the government has issued various policies. Firstly, the policy relating to the substance of the law, the government has passed various laws and ratified international conventions. Secondly, the regulations concerning law enforcement agencies, the government has established the Corruption Eradication Commission, Corruption Crime Court, the Center for Reporting and Analyzing Financial Transactions (PPATK), the Witness and Victim Protection Agency (LPSK), and the establishment of internal supervisory bodies. However, these efforts seemingly face failure. The facts show that corruption increases in the executive, legislative and judicial institutions, from the center to the region level. The failure of corruption eradication can be one of the reasons that indicates the formulation of criminal sanctions in Law No. 20/2001 for corruption is weak, not appropriate for the negative impacts of the crime. Consequently, the punishment imposed has no deterrent effect for either the perpetrators or others. It is contrast to the concept of sanctions in Islamic criminal law, sanctions imposed on the perpetrators must be comparable with their evil deeds (Qur'an Surah 42, verse 40), with the aim to benefit for human both individual and collective. According to the Â concept, this article will examine criminal sanctions based on Islamic criminal law as an eradication strategy of corruption. The results of this article can be a consideration for the revision of the framework in formulating criminal sanctions contained in Law No. 20 / 20011 concerning corruption.